The Promotion Strategy For Wedding Packages: A Case Study Of JW Marriott Hotel Surabaya - Alleigra Devi Rossadeane; Rean Mitasari (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2026)
The MICE industry in Indonesia is projected to grow significantly, with Surabaya emerging as a key hub for meetings and events. This study examines the promotion mix strategies employed by JW Marriott Hotel Surabaya to market its wedding packages within a competitive hospitality landscape. Using a qualitative descriptive approach with thematic analysis, data were collected through semi-structured interviews with two Wedding Sales Managers and three clients, complemented by observation and document analysis. The findings reveal that the hotel's promotional strategy centers on three primary elements: digital advertising reinforced by organic word-of-mouth, consultative personal selling that prioritizes client needs over transactional approaches, and value-added sales promotions that preserve premium brand positioning. Public relations and direct marketing were excluded from the active promotion mix, as contemporary wedding clients demonstrate greater reliance on peer recommendations and social media evidence than on corporate-led communication. A distinctive characteristic of the strategy is its cultural attunement, reflected in the timing of wedding exhibitions during Ramadan and the Suro month, and accommodation of local preferences such as individual set menu dining. The study concludes that authentic service delivery functions as the hotel's most powerful self-sustaining promotional tool, offering a replicable framework for luxury hospitality venues seeking differentiation beyond price competition.